Volume 21: Solar Terrestrial (ST)
DOI: 10.1142/9789812838209_0016
|View full text |Cite
|
Sign up to set email alerts
|

Drift Effects and the Average Features of Cosmic Ray Density Gradient in Cirs During Successive Two Solar Minimum Periods

Abstract: We deduce on hourly basis the spatial gradient of the cosmic ray density in three dimensions from the directional anisotropy of high-energy (∼50 GeV) galactic cosmic ray (GCR) intensity observed with a global network of muon detectors on the Earth's surface. By analyzing the average features of the gradient in the corotational interaction regions (CIRs) recorded in successive two solar activity minimum periods, we find that the observed latitudinal gradient (Gz) changes its sign from negative to positive on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…This drift model prediction of G z has been actually confirmed by previous analyses of the GMDN and NM data (Chen & Bieber 1993;Okazaki et al 2008;Fushishita et al 2010a;Munakata et al 2014;Kozai et al 2014).…”
Section: Gcr Density Gradient Perpendicular To the Ecliptic Planesupporting
confidence: 81%
See 3 more Smart Citations
“…This drift model prediction of G z has been actually confirmed by previous analyses of the GMDN and NM data (Chen & Bieber 1993;Okazaki et al 2008;Fushishita et al 2010a;Munakata et al 2014;Kozai et al 2014).…”
Section: Gcr Density Gradient Perpendicular To the Ecliptic Planesupporting
confidence: 81%
“…Following theoretical calculations by Bieber et al (2004), we assume in this paper constant α and α ⊥ at α = 7.2 and α ⊥ = 0.05α . This assumption is also used by Okazaki et al (2008) and Fushishita et al (2010a) and proved to result in a reasonable GCR density distribution in the vicinity of the interplanetary disturbance. Moreover, Fushishita et al (2010b) deduced the parallel mean free path λ from the observed "decay length" of the loss-cone precursor of an IP-shock event and obtained λ comparable to our assumption of λ = 7.2R L .…”
Section: Derivation Of the Density Gradient Vectormentioning
confidence: 94%
See 2 more Smart Citations
“…the simplest adiabatic heating of cosmic rays, is a possible cause of the cosmic-ray increase observed near the trailing edge of MFR in this paper, as discussed above, although we do not know any literatures reporting the compressive heating of plasma or energetic ions/electrons inside an MFR near the trailing edge. On the other hand, there are other possibilities to observe the cosmic-ray increase, because steady structures such as the heliospheric current sheet and corotating interaction region affect the drift of cosmic rays and can also modulate the large-scale spatial distribution of cosmic-ray density and anisotropy (Fushishita et al, 2010;Okazaki et al, 2008). This study therefore provides an important clue to examine cosmic-ray diffusions parallel and perpendicular to the IMF, and the dependence on the IMF magnitude in great detail, via close collaborations with the drift-model simulations of cosmic-ray transport (Miyake et al, 2017) and the cutting-edge MHD simulations (Matsumoto et al, 2019;Shiota and Kataoka, 2016).…”
Section: Discussionmentioning
confidence: 99%